A Study of Flow Pattern and Sedimentation in Hydraulic Physical Model - Khan M.N.N.; Zainol M.R.R.M.A.; Ahmad M.A.; Zahari N.M.; Zawawi M.H.; Radzi M.R.M.; Aziz N.A.; Ghazali F.N.C.; Abas M.A. (Springer Nature, 2024)
Sustainability of hydroelectric dams has been questioned due to the sedimentation, erosion and vortex formation at the dams. This study had assessed the potential of sedimentation, erosion and vortex formation based on the flow pattern formed via hydraulic physical model (Scale of 1:100). Four cases have been tested which are Case 1 (the position of water inlet at the middle with stage of 0.38 m), Case 2 (the position of water inlet at the middle with stage 0.34 m), Case 3 (the position of water inlet at the side with stage of 0.38 m) and Case 4 (the position of water inlet at side with stage 0.34 m). Based on Case 3, the range of flow velocities obtained was 0.32.1m/s at 20% from water surface, leading to erosion at the dam bank and sedimentation which focused on the side of the dam that threatened the stability of the dam due to the concentrated load of sediment. Vortex type 56 had been identified for a period of 1530 s. Overall, the flow pattern at the dam up-stream was influenced by the position of water inlet from dams upstream, flowrate of the dam and the depth from the water level. The Author(s), under exclusive license to Springer Nature Switzerland AG 2023.